Public Country-by-Country Reporting: Corporate Law, Fiscal Law and the Principle of Unanimity - Schön, Wolfgang (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article deals with the reporting obligations laid down by the European Commission, Proposal for a Directive of the European Parliament and of the Council amending Directive 2013/34/EU of 1 June 2021 (so-called “public country-by-country reporting”) obliging certain corporate income taxpayers to disclose to the general public sensitive business information i.e., number of employees, level of pre-tax profits, level of taxes accrued, and taxes paid designed to prevent and to sanction corporate tax avoidance. The Author discusses whether such rules can be introduced based on the majority vote or on the basis of unanimity.